Entrepreneurial Orientation, Innovation, Ecosystem, and Digital Literacy on Venture Growth via Opportunity Recognition - Ulfi Hanifah, Risti; Rizki Nugraha, Aditya (Journal Economic Business Innovation, 2025)
Purpose: The main objective of the study is to study the impact of entrepreneurial orientation, innovation capability, entrepreneurial ecosystem support, and digital literacy on firm growth considering opportunity recognition as a mediating variable. Method: Quantitative research was through a questionnaire distributed to 235 entrepreneurial actors in Java Island and of Yogyakarta Special Region with 43 samples determined with purposive sample technique. Data were processed in SPSS, where descriptive statistics, Pearson correlation, reliability analysis, multiple regression, and mediation. Findings: The findings of this study indicate that four antecedents namely entrepreneurial orientation, innovation capability, ecosystem support, and digital literacy have a positive influence on growth of venture. Opportunity recognition mediates the relationship between the individual variables and venture growth, thus underlining the importance of this factor in the transformation of strategic entrepreneurial resources into performance outcomes. Novelty: The current study proposes an integrative model linking four categories of antecedents with a mediating cognitive mechanism (opportunity recognition), supplementing previous, partial explanations. It offers empirical evidences in an emerging market setting where the entrepreneurial ecosystem and digital literacy play an increasingly role not thoroughly covered. Implications: The current study proposes an integrative model linking four categories of antecedents with a mediating cognitive mechanism (opportunity recognition), supplementing previous, partial explanations. It offers empirical evidences in an emerging market setting where the entrepreneurial ecosystem and digital literacy play an increasingly role not thoroughly covered